Early versus delayed postoperative extubation after elective neurosurgical treatment of brain metastasis - Logman Khalafov; T. Lampmann; M. Hamed; J. Dittmer; I. Maiseyeu; H. Alenezi; M. Jaber; H. Asoglu; M. Thudium; F. Lehmann; S. Ehrentraut; J. Poth; et al. (Journal of Cancer Research and Clinical Oncology)
Abstract Introduction It is generally assumed that early extubation after elective neurosurgical treatment of brain metastases (BMs) is associated with a lower rate of adverse events (AE), such as an increased rate of respiratory infections. The aim of this study is to investigate to what extent this association holds for the patient cohorts of our clinic who underwent elective intracranial surgery and whether in our experience early extubation (EE) was inferior to delayed extubation (DE). Material and methods Between 2018 and 2020, 190 patients were surgically treated for BM in the authors’ neurosurgery department. Early extubation was defined as extubation immediately after surgery in the recovery room. The DE group was electively extubated after surgery in the intensive care unit. We analyzed demographic data, ASA status, blood loss, comorbidities, duration of surgery, blood transfusion, length of hospital stay, surgical-related complications and adverse events. Results A total of 65 patients (34.2%) were extubated early. In the remaining 65.8% of patients extubation was delayed. In the univariate analysis, no statistical significance was found between the two groups, particularly with regard to complications. The only relevant difference was in the DE group, who had greater transfusion requirements (p = 0.037). The DE group showed more AE, but this was not significant in the multivariate analysis. Conclusions Our data demonstrate that early extubation was justifiable and safe for our patients. Early extubation in the recovery room did not pose a risk of re-intubation immediately after elective neurosurgical resection of a brain metastasis.